2014
DOI: 10.1146/annurev-physiol-021113-170338
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms for Synchronous, Asynchronous, and Spontaneous Neurotransmitter Release

Abstract: Most neuronal communication relies upon the synchronous release of neurotransmitters, which occurs through synaptic vesicle exocytosis triggered by action potential invasion of a presynaptic bouton. However, neurotransmitters are also released asynchronously with a longer, variable delay following an action potential or spontaneously in the absence of action potentials. A compelling body of research has identified roles and mechanisms for synchronous release, but asynchronous release and spontaneous release ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
441
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(454 citation statements)
references
References 217 publications
13
441
0
Order By: Relevance
“…These results indicate that local regulation of Ca V 2.1 channels by Ca 2+ entry and binding to CaM and other CaS proteins is entirely responsible for short-term synaptic plasticity that depends on local Ca 2+ transients in hippocampal SC-CA1 synapses. The remaining half of synaptic facilitation in IM-AA synapses evidently depends on more global changes in Ca 2+ concentration that cause facilitation because of changes in endogenous Ca 2+ buffers, regulation of SNARE protein function, or docking synaptic vesicles closer to Ca V 2.1 channels (1,3,4,(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that local regulation of Ca V 2.1 channels by Ca 2+ entry and binding to CaM and other CaS proteins is entirely responsible for short-term synaptic plasticity that depends on local Ca 2+ transients in hippocampal SC-CA1 synapses. The remaining half of synaptic facilitation in IM-AA synapses evidently depends on more global changes in Ca 2+ concentration that cause facilitation because of changes in endogenous Ca 2+ buffers, regulation of SNARE protein function, or docking synaptic vesicles closer to Ca V 2.1 channels (1,3,4,(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…7E), in agreement with the specific slowing of synaptic depression by synapsin IIa. Recently, it was reported that synapsin II progressively desynchronizes synaptic release during trains of stimuli in GABAergic neurons (Medrihan et al, 2013), an effect that can increase the charge transfer during a train of stimulation over and above the observed effect on the amplitude (Kaeser and Regehr, 2014). We measured the ratio between the charge and the amplitude of the EPSCs throughout the train to assess whether response desynchronization may contribute to the observed effect on the charge transfer.…”
Section: Atp Binding By Synapsin Iia Is Essential For Its Ability To mentioning
confidence: 97%
“…The aforementioned experiments address the effect of the ATPbinding site on the steady-state vesicle density within resting terminals, but do not explore a possible role for changes in [ATP] syn in acute activity-dependent redistribution of vesicles (Kamin et al, 2010). Limited redistribution of SypI has been reported to take place during stimulation of neurons in a manner that could indicate intracellular redistribution of vesicles (Li and Murthy, 2001), although this observation has been interpreted to reflect mostly the diffusion of exocytosed synaptophysin within the axonal membrane.…”
Section: Atp Binding By Synapsin Iia Does Not Affect Acute Vesicle Rementioning
confidence: 99%
See 1 more Smart Citation
“…Syt1 is one of the most well-studied vesicle trafficking proteins and functions to sense Ca 2+ influx and regulate fusion of SVs (Littleton et al 1993(Littleton et al , 2001aBroadie et al 1994;Diantonio and Schwarz 1994;Reist et al 1998;Yoshihara and Littleton 2002;Mackler et al 2002;Saraswati et al 2007;Yoshihara et al 2010;Jorquera et al 2012;Striegel et al 2012;Lee et al 2013b;Lee and Littleton 2015). Neurotransmitter release is characterized by a synchronous phase of SV fusion that occurs within milliseconds, and a slower asynchronous component that can last for hundreds of milliseconds depending on the synapse (Kaeser and Regehr 2014). Drosophila syt1 null mutants lack the fast synchronous component of evoked fusion and show enhanced asynchronous and spontaneous release as well ( Figure 2B) (Littleton et al 1993;Yoshihara and Littleton 2002;Yoshihara et al 2010;Jorquera et al 2012;Lee et al 2013b;Lee and Littleton 2015).…”
Section: Synaptotagminmentioning
confidence: 99%